2013
DOI: 10.3389/fncel.2013.00045
|View full text |Cite
|
Sign up to set email alerts
|

Origin and differentiation of microglia

Abstract: Microglia are the resident macrophage population of the central nervous system (CNS). Adequate microglial function is crucial for a healthy CNS. Microglia are not only the first immune sentinels of infection, contributing to both innate and adaptive immune responses locally, but are also involved in the maintenance of brain homeostasis. Emerging data are showing new and fundamental roles for microglia in the control of neuronal proliferation and differentiation, as well as in the formation of synaptic connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
557
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 704 publications
(587 citation statements)
references
References 150 publications
3
557
1
2
Order By: Relevance
“…In order to study CX3CR1 on microglia specifically, we made bone marrow (BM) chimeras using WT and CX3CR1-null mice as hosts and congenically marked WT BM as the donor (Supplemental Figure 3A). As microglia are radioresistant and should remain of host origin after irradiation (32), this experimental design allows for comparison of WT and CX3CR1-null microglia after ICH in mice with an otherwise WT immune compartment. CX3CR1-null microglia had a significant reduction in TGF-β1 gene expression at 14 days compared with WT microglia.…”
Section: Resultsmentioning
confidence: 99%
“…In order to study CX3CR1 on microglia specifically, we made bone marrow (BM) chimeras using WT and CX3CR1-null mice as hosts and congenically marked WT BM as the donor (Supplemental Figure 3A). As microglia are radioresistant and should remain of host origin after irradiation (32), this experimental design allows for comparison of WT and CX3CR1-null microglia after ICH in mice with an otherwise WT immune compartment. CX3CR1-null microglia had a significant reduction in TGF-β1 gene expression at 14 days compared with WT microglia.…”
Section: Resultsmentioning
confidence: 99%
“…37) Thus, microglia occupy a central position in the defense and maintenance targets in neurological disorders and recovery from brain injury. 38) To explore the anti-neuroinflammatory mechanism of compounds 3 and 9, the mRNA expression levels of iNOS and COX-2 were examined by quantitative real time PCR. Real time RT-PCR analysis showed that compounds 3 and 9 significantly down-regulated the mRNA expressions of iNOS and COX-2 in a concentration-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the CNS, pattern-recognition receptors are primarily expressed by microglia, macrophages, and astrocytes. Microglia cells are often termed the "sentinel of brain parenchyma" because they are constantly in a state of alert to detect pathogen's invasion through the pattern-recognition receptors (PRR) that they express [116]. They can display two different types of receptors: Toll-like receptors (TLRs) that are membrane spanning receptors, and Nod-like receptors (NLRs), which are cytoplasmic sensors able to oligomerize and form a platform for the inflammasome [115,117].…”
Section: Inflammasome Activationmentioning
confidence: 99%